Common practices of three local manufacturing companies in managing garment seconds - Balmaceda, Joy Renos; Escano, Ma. Monica R. (2003.)
Garment seconds are products that do not meet quality specification. Despite an industry- wide effort to implement quality, perfection in manufacturing is still not reached. This arises from the fact that manufacturing involves several factors such as human workers and even the processes involved. Some of these factors are subject to imperfections and are difficult or impossible to be manipulated or controlled. On the other hand, second quality garments are still part of the inventory and cost. Although they do not make up the greater percentage of production, it is still important to manage or treat and dispose them properly to gain back the investment made to produce them. The focus of this study is on the general practices that garment manufacturers conduct regarding garment defects management. The respondent companies are all Metro Manila-based and local distributors. This study used the comparative method to analyze information gathered through survey questionnaire. The questionnaire, which was guided by short interview, used the Garment Defects identified by the Philippine Trade and Training Center. The key findings of the study are the following: 1)The most common practice of the three selected local manufacturing companies in managing garment seconds is to sell them as seconds without reworking. 2) Majority of the defects encountered which caused their garments to be classified as seconds may be caused by the sewing process. 3) In managing seconds, these companies considered several factors such as the degree of defect, cost of production and the time consumed in production. 4) In marketing seconds, they consider location, time frame and the pricing strategy.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing factories -- Philippines -- Management